(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
The prognostic relevance of intratumoral stromal mast cells (MCs) in renal cell carcinoma (RCC) remains insufficiently investigated and controversial. The present study aimed to evaluate the quantitative characteristics of stromal mast cells in RCC and to analyze their relationship with major clinical, anatomical, and histopathological prognostic factors.